2010
DOI: 10.3382/ps.2010-00655
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and carcass and meat quality of broiler chickens fed diets containing micronized-dehulled peas (Pisum sativum cv. Spirale) as a substitute of soybean meal

Abstract: An experiment was carried out to evaluate the effects of diets containing peas on productive traits, carcass yields, and fatty acid profiles (breast and drumstick meat) of broiler chickens. Hubbard strain broiler chicks, divided into 2 groups, received from 14 d to slaughtering age (49 d) a wheat middlings-based diet containing soybean (190 g/kg) or micronized-dehulled peas (400 g/kg) as the main protein source. The inclusion of peas did not significantly change the growth performance of birds. The pea level h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
60
5
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 27 publications
26
60
5
8
Order By: Relevance
“…Savage et al(1986) have reported that the differences for the content of abdominal fat between the male and female turkeys fed from 20% to 55% peas and the turkeys of the control groups were respectively 0.46-0.67% and 1.13-1.36%, but this difference was insignificant (P > 0.05). This, regarding the abdominal fats, is in agreement with the findings of Bekric et al (1990) and Laudadio and Tufarelli (2010) in their trials with chicken broilers fed, respectively, 27% and 40% peas. The breast muscle content of males in the trial groups was from 0.44% to 1.83% lower in comparison with the control group, but this difference was insignificant.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Savage et al(1986) have reported that the differences for the content of abdominal fat between the male and female turkeys fed from 20% to 55% peas and the turkeys of the control groups were respectively 0.46-0.67% and 1.13-1.36%, but this difference was insignificant (P > 0.05). This, regarding the abdominal fats, is in agreement with the findings of Bekric et al (1990) and Laudadio and Tufarelli (2010) in their trials with chicken broilers fed, respectively, 27% and 40% peas. The breast muscle content of males in the trial groups was from 0.44% to 1.83% lower in comparison with the control group, but this difference was insignificant.…”
Section: Resultssupporting
confidence: 81%
“…This is in agreement with the studies of Savage et al (1986), who conducted a similar trial with peas and obtained the same results, with the study of Christodoulou et al (2006) where turkeys were fed from 20% to 80% of chickpeas (Cicer arietinum L.) and also with the studies of Laudadio and Tufarelli (2010) and Nalle (2009), who conducted trials with chicken broilers (20-40% peas) and found no relationship between the breast and thigh muscle percentage and weight of internal organs in relation to the feed composition. Conversely to the studies of Savage et al (1986) and Christodoulou et al (2006) who found no correlation between the content of female abdominal fat and the content of peas or chickpeas in the diet or gender Table 2.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…However, increasing demand for soybean meal, associated with the increase in poultry production worldwide, has resulted in increased prices (Laudadio and Tufarelli 2010). Due to low protein content, amino acid imbalances, and the presence of anti-nutritional factors, few plant protein sources are suitable as replacements for soybean meal in poultry diets (Rubio et al 2003).…”
Section: Discussionmentioning
confidence: 99%